Papvimochneshwar Temple dedicated to Lord Shiva - Mumbai Archive Project Team (Jio Institute, 2024)
Papvimochneshwar Temple is dedicated to Lord Shiva and was built around a self-manifested (syambhu) lingam in the inner sanctum (garbagriha). A marble Nandi sits in the mandapa facing the sanctuary.